Study guides

☆☆

Q: What is the derivative of 2x2 plus 3x plus 7?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

4x

(2x + 7)(x - 2)

f(x) = 3x4 - 2x2 + 7f ' (x) = 12x3 - 4xf ' ' (x) = 36x2 - 4

(2x + 7)(x - 2)

2x2 - 3x + 7 = 0 doesn't factor neatly. Applying the quadratic formula, we find two imaginary solutions: (3 plus or minus the square root of -47) divided by 4.x = 0.75 + 1.713913650100261ix = 0.75 - 1.713913650100261iwhere i is the square root of negative 1

Related questions

2x2 equals 5

4x

(2x + 7)(x - 2)

(x-2)(2x+7)

65

f(x) = 3x4 - 2x2 + 7f ' (x) = 12x3 - 4xf ' ' (x) = 36x2 - 4

(2x + 7)(x - 2)

(2x + 7)(x - 2)

2x2 - 3x + 7 = 0 doesn't factor neatly. Applying the quadratic formula, we find two imaginary solutions: (3 plus or minus the square root of -47) divided by 4.x = 0.75 + 1.713913650100261ix = 0.75 - 1.713913650100261iwhere i is the square root of negative 1

=3x+7

2x2 + 21x + 49 = 2x2 +14x +7x + 49 = 2x(x + 7) + 7(x + 7) = (2x + 7)(x + 7)

10x + 7 + 3x = 13x + 7